(untitled) - Gobat, Jean-Michel (Enfield, NH., 2004)
This study looks at the fundamentals of soil science and soil biology, encompassing topics such as the building blocks of the soil system and bioremediation of contaminated soils.
Sử dụng phế thải sinh học trong sản xuất phân hữu cơ,Sinh học đất
Keywords: Soil science,Plant-soil relationships,Soil biology